0444 The effect of distinct components of CBT-I on slow wave power and energy. (25th May 2022) - Ahmadi, Maryam; Krause, Adam; O'Hora, Kathleen; Hernandez, Beatriz; Lazzeroni, Laura; Zeitzer, Jamie; Friedman, Leah; Posner, Donn; Kushida, Clete Kushida clete@stanford edu; Yesavage, Jerome; Saletin, Jared; Goldstein-Piekarski, Andrea
Abstract: Introduction: Cognitive-behavioral therapy for insomnia (CBT-I) is an effective multi-component treatment known to improve sleep in older adults with insomnia, including increasing NREM slow-wave activity (SWA) EEG power (0.5 – 4.75Hz) and sleep depth. However, the relative contributions of distinct components of CBT-I to changes in SWA remain unknown. Methods: We examined the relative impact of specific components of CBT-I: behavioral therapy (sleep restriction + stimulus control) (BT), cognitive therapy (CT), and combined BT and CT (CBT) on SWA in 111 older adults (75 female; mean age: 69±6.1 years) with insomnia (Insomnia Severity Index >10). Participants underwent polysomnography (PSG) at baseline prior to being randomized to a 6-session treatment regimen of BT, CT, or CBT. PSG was reassessed immediately following treatment and at 6-months follow-up. We computed SWA and time-accumulated slow-wave energy (SWE) at each time point. Mixed-effects models compared treatment efficacy on SWA and SWE outcomes. Results: We identified significant time-by-treatment interactions for both SWA (B=0.69, t=2.14, p=0.034) and SWE (B=0.93, t=1.98, p=0.049). Post-hoc tests revealed that SWA/SWE increased from baseline to the end of treatment for CT group (SWA: d=0.42, SWE: d=0.54), while there were limited changes in the BT (SWA: d=0.27, SWE: d=0.29) and in the CBT groups (SWA: d=0.18, SWE: d=0.06). These changes were absent at 6-month follow up. Conclusion: Our preliminary results indicated that different components of CBT-I have distinct effects on SWA/SWE with CT alone indicating improved NREM sleep quality. Given previous findings of lower SWA for sleep misperceptors underestimating their sleep depth, compared with good-sleepers, this result may suggest that reducing misperception of sleep with CT increases SWA/SWE. Further study is needed to dissociate the effect of BT from CT in combined CBT-I. Support (If Any):